Effect of calcium carbonate onmechanical and thermal properties of kenaf recycle polypropylene/polyethylene wood plastic composites - Nur Fatin Nadia, Ahmad (2016)
Wood recycle plastic composite (WrPC) was prepared using kenaf wood flour, recycle polypropylene (rPP), recycle polyethylene (rPE) and maleic anhydried polypropylene (MAPP) in the presence of calcium carbonate (CaCO3) filler. Kenaf wood flour, rPP, rPE, MAPP were premixed manually and fed into single-screw extruder. Universal tensile machine (UTM) and izod impact were used to study the mechanical properties. Differential scanning calorimeter (DSC) and thermalgravimertric analysis (TGA) were used to study the thermal properties. Scanning electron microscope (SEM) was used to investigate the morphology. The effect of CaCO3 on mechanical properties, thermal properties and morphology were studied. Tensile strength of WrPC was increase from 7.72 MPa to 8.26 MPa due to transfer of stress from polymer matrix to CaCO3 particles. Impact strength was decrease from 7.14 KJ/m2 to 6.14 KJ/m2 due to the improved stiffness of the composites which was attributed to interaction between the polymer and CaCO3 fillers. Prepared WrPC exhibit two Tg as a result from immiscible blend of Kenaf, rPP, rPE and CaCO3. Tg2 of WrPC with CaCO3 loading slightly increased from 162°c to 163°c due to strong interfacial interaction between CaCO3 and kenaf/rPP/rPE, which reduced the free volume and restricted the motion of rPP and rPE chains. Besides, decomposition of WrPC was affected by the addition of CaCO3. CaCO3 loading prohibits complete combustion of the sample since the degradation temperature of CaCO3 is high. The internal structures of WrPC have better dispersion and fewer voids.